(untitled) (Revista de Estudos da Linguagem, 2020)
Abstract: This paper addresses the issue of multimodal re-performance, a concept developed by us, in view of the fact that the famous song “Imagine”, by John Lennon, was published in illustrated book format by Frances Lincoln Children’s books under the sponsorship of Amnesty International in 2017 and later in an English-Portuguese bilingual edition in 2018 by Edicare. From our point of view, the concept of multimodal re-performance builds on the “personal authorization” criterion, a prominent feature in the legitimization of discourse and communication (VAN LEEUWEN, 2007), which we address in the light of the Multimodal Metaphor approach (FORCEVILLE, 2009, 2017). In conformity, we advocate that multimodal metaphorical links of different kinds in this re-performed edition of “Imagine” are architectured by a relevantly harmonious set of three communication modes: J. Lennon’s original song lyrics in the multimodal mode, the book’s preface by Yoko Ono in close connection to the book’s epilogue by Amnesty International, also in the written mode, and Jean Jullien’s brilliant illustrations in the visual mode. Last but not least, it is highlighted that this appealing re-performed multimodal cultural product “Imagine” is crafted with the purpose of both foregrounding the updated message of Imagine’s PEACE quest protagonized by the brown PEACE dove. Furthermore, in the epilogue, the reader is encouraged to visit the webpage https://imaginepeacebook.com and leave a peace message behind, opening the possibility for extension of the written mode echoing the song’s message in the future. Keywords: multimodal re-performance; personal authorization; multimodal metaphor; Imagine by J. Lennon. Resumo: O presente incide sobre a questão da re-performance multimodal, um conceito desenvolvido por nós, tendo em vistaa publicação da famosa canção “Imagine” de John Lennon, em formato de livro ilustrado pela editora de livros infantis Frances Lincoln, com o patrocínio da Amnistia Internacional e posteriormente dado à estampa pela Edicare numa versão bilingue inglês-português. Na nossa perspetiva, o conceito de re-performance multimodal está ancorado no conceito de “autorização pessoal”, um parâmetro proeminente na legitimação do discurso e da comunicação (VAN LEEUWEN, 2007) que desenvolvemos à luz da abordagem da metáfora multimodal (FORCEVILLE, 2009, 2017). Em conformidade com a mesma, advogamos que as conexões metafóricas multimodais de diferentes tipos nesta edição re-performada do “Imagine” são arquitetadas na base da articulação harmoniosa de três modos de comunicação: a canção original da autoria de J. Lennon, já de si um produto multimodal, o prefácio do livro, elaborado por Yoko Ono, em estreita ligação com o epílogo da obra da autoria da Amnistia Internacional, sob a forma de modo escrito, e as brilhantes ilustrações de Jean Jullien, no modo visual. Por último, pretende-se sublinhar que este “Imagine” enquanto produto multimodal re-performado, muito apelativo, destina-se a pôr em destaque a atualidade da mensagem do “Imagine” , na sua versão original, enquanto apelo à PAZ, protagonizada por uma pomba castanha. Além do mais, no epílogo, o leitor é encorajado a visitar a página https://imaginepeacebook.com e a deixar escrita uma mensagem de paz, abrindo a possibilidade para uma extensão do modo escrito fazendo eco da mensagem da canção, no futuro. Palavras-chave: re-performance multimodal; autorização pessoal; metáfora multimodal e Imagine de J. Lennon.